Anatomia foliar de pedra-hume-caá (Myrcia sphaerocarpa, Myrcia guianensis, Eugenia punicifolia - Myrtaceae) - Jorge, Uzia I. F.; Aguiar, Jaime Paiva Lopes; Silva, Maria de Lourdes P. (Acta Amazonica, 2000)
The anatomy and morphology of the leaves of Myrcia multiflora (Lam.) DC, Myrcia guianensis (Aubl) Urb. and of Eugenia punicifolia (H. B. K.) DC. are described. Although these species show the universal characteristics of the Myrtaceae, they also present some peculiarities that allow their identification and the recognition of fraud, intentional or not. The main characteristic histological elements of these species are: ornamentation of the cuticle, stomata types, outline of epidermal cells in surface view and types and comparative abundance of inorganic cellular inclusions.
Foliar anatomy of pedra-hume-caá (Myrcia sphaerocarpa, Myrcia guianensis, Eugenia punicifolia, Myrtaceae)
Keywords: Myrcia Sphaerocarpa; Eugenia Punicifolia; Myrcia Guianensis; Leaf Morphology; Leaf Anatomy; Myrcia Sphaerocarpa; Eugenia Punicifolia; Myrcia Guianensis; Morfologia Foliar; Anatomia Foliar